Decision Making in the Perspective of Sundanese Culture and Its Implications in Guidance and Counseling - Fatimah, Siti; Suminar, Riani (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
This study aims to analyze career decision-making skills from a Sundanese cultural perspective which is characteristic of Sundanese culture, Sundanese people's interests are synonymous with less challenging career choices and the difficulty of making career decisions because they adhere to the life principle